Investigation of efficient mixing enhancement in planar micromixers with short mixing length - Yuan, Shuai; Jiang, Bingyan; Peng, Tao; Zhou, Mingyong; Drummer, Dietmar (Chemical Engineering and Processing, 2022)
Achieving rapid mixing of different liquids in a short distance is important for biochemical applications. Here, a new type of micromixers consisting of double symmetrical V-shaped baffles (MMA and MMB mixers) and double asymmetrical V-shaped baffles (MMC and MMD mixers) is proposed. Numerical simulations are performed to evaluate their mixing performance when the Reynolds number (Re) ranges from 0.1 to 50. Meanwhile, the visualization of vortex formation is conducted to analyze the mixing mechanism. The results show that the mixing efficiency of all mixers approaches 0.8 for all Re at the short distance of 3500 μm. At relatively low Re=0.5, the MMA and MMB perform better than MMC and MMD due to more adequate molecular diffusion; whereas the unbalanced lateral flows and multidirectional vortices in the MMC and MMD induce stronger chaotic convection at high Re=50, leading to a higher performance. Moreover, the disturbance created by the vortex on the mass transfer surface is not only relying on its vorticity but also correlates with the position of vortex/vortex leg. Lastly, all micromixers are fabricated, tested and compared with the simulation results and both of them show a good agreement.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Chaotic advection; Planar micromixer; V-shaped baffle; Vortex